Impact of a Collaborative Flipped Classroom with Think-Pair-Share on Physics Problem-Solving Skills - Wahyuni Handayani; Kanya Adwasyifa; Ade Yeti Nuryantini (Science Education and Application Journal, 2025)
This study aims to enhance students’ problem-solving skills in physics, specifically in simple harmonic motion, by implementing a collaborative flipped classroom (FC) model based on discovery learning and the think-pair-share (TPS) method. Using a quasi-experimental design with a non-equivalent control group, the research involved 30 high school students in West Java across two classes. The experimental group participated in flipped classroom activities that incorporated TPS, where students worked in pairs to discuss and explain concepts. Pre-class sessions focused on conceptual understanding, while in-class activities emphasized problem-solving. Both groups received an e-learning module developed by the researchers, which included material descriptions, instructional videos, and guided worksheets. The experimental group showed a significantly higher N-gain (0.85) compared to the control group (0.64), with statistical analysis (independent T test, p<0.005) confirming a significant improvement in problem-solving skills.